Municipal solid waste incineration slag as potential materials in green engineering as partial or total substitutes for conventional cement in future decades - Sebastião Ventura; Lino Maia (Discover Applied Sciences)
Abstract In the context of this research to characterize the slags from the incineration of municipal solid waste as potential supplementary cementitious materials, the principle of comparative analysis of the physical, chemical and mechanical potentials of the Portland cement. Was chosen, complemented with SlagFlyAsh in some specific cases. The bases of objective study, we had two slags matured and ground during one night with a weight equal to 25% of the weight of the balls in the mill, designated SlagMat1n25%, as well as another slag matured with grinding in the same duration of one night and with a weight equal to 50% of the weight of the balls in the mill designated SlagMat1n50%, as well as another unmatured slag called SlagNMatLL. The percentage proportions of the oxides as main elements and a description of the minor constituent elements in the materials were also determined and presented, thus allowing the elaboration of an analytical table demonstrating the nature of the oxide, namely its molar mass, density, melting and boiling point, as well as the nature of its crystalline structure, all in the chemical part. Also, in the main oxide elements, the ternary phase diagram, the silica and alumina modules, as well as the lime saturation factor were analyzed. Also, the potential reactivity to alkalis of the aggregates, as well as the determination of the Electrical Resistivity.